O trabalho do enfermeiro de um hospital pediátrico de ensino e o SUS: desafios a enfrentar - Mororó, Deborah Dinorah de Sá (2006)
This study analyzes the point of view of nurses working at a pediatric teaching hospital on their work process within the scope of the Brazilian unified healthcare system SUS, in order to identify factors that interfere with its development and find out how work relations are taking place between nurses, other nursing professionals and the multidisciplinary staff. It is a descriptive and analytical study, qualitative in nature, which starts with a consideration of a nurse s current practices and moves on to reflect on a perspective of transformation aiming at rethinking their work process pursuant to the principles of SUS. In order to attain these objectives, we decided on using the focal group as a data-collecting technique, which took place from November to December 2005, by using as instruments a questionnaire for the characterization of the persons being researched and a discussion outline. Theoretical support has approached transformations in the world of work, placing it in the context of healthcare and nursing and has tried, specifically, to understand the work process of a nurse engaged in the production of health services. Therefore, the discourse analysis of participants, in the light of theoretical support, has evinced an ambiguity inasmuch as though identified as such in their work process, nurses are also fulfilling multiple functions in health services. Through this study it has also been possible to identify several factors that interfere with the work of these professionals, including poor working conditions and excessive hiring of high school graduate interns as an attempt to make up for a meager nursing workforce, as well as reveal the possibilities brought about by the SUS in retargeting its professional practice to interdisciplinarity and integrality